2008
DOI: 10.1007/s12325-008-0114-y
|View full text |Cite
|
Sign up to set email alerts
|

The role of erythropoietin in hemorrhagic shock-induced liver and renal injury in rats

Abstract: These results suggest that EPO is effective in attenuating liver and renal injury in HS, even with inhibition of tyrosine kinase activity with genistein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 46 publications
(77 reference statements)
0
4
0
Order By: Relevance
“…In studies examining liver I/R damage in HS, rhEPO was shown to prevent liver damage. Comparision of effects of intravenous EPO given 60 minutes before and 30 minutes after experimental HS in rats in a study revealed that EPO is more effective in reducing liver damage if it is given before HS occurs (12). In a later experimental HS study, it was shown that EPO given three hours before the induction of HS significantly attenuated renal, hepatic and neuromuscular injury and dysfunction caused by HS (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies examining liver I/R damage in HS, rhEPO was shown to prevent liver damage. Comparision of effects of intravenous EPO given 60 minutes before and 30 minutes after experimental HS in rats in a study revealed that EPO is more effective in reducing liver damage if it is given before HS occurs (12). In a later experimental HS study, it was shown that EPO given three hours before the induction of HS significantly attenuated renal, hepatic and neuromuscular injury and dysfunction caused by HS (13).…”
Section: Discussionmentioning
confidence: 99%
“…In studies investigating post-MI liver tissue, the effects of betaine (an essential organic osmolyte) (3) and tribulus terrestris (a fruit) (5) have been examined. Previous studies on ischemic liver mostly focused on cold ischemia and reperfusion during liver transplantation (6)(7)(8)(9)(10)(11) or hemorrhagic shock (12)(13)(14). Studies investigating the effects of erythropoietin (EPO), which is the main hemopoietic hormone, for the prevention of cold ischemia in the liver that occur during transplantation started with Yilmaz (11).…”
Section: Introductionmentioning
confidence: 99%
“…5a). It has been reported that unbalanced immunoinflammatory reactions triggered by shock or trauma are linked to multiple organ failure, and multiple organ failure is the primary cause of the increased morbidity and mortality in patients with severe trauma or hemorrhagic shock (Bahrami et al 2006;Algin et al 2008). More specifically, the increase in systemic proinflammatory cytokines was associated with cellular injury and remote organ dysfunction, and these cytokines have been reported to play a role in the complex development mechanism of aggravated hepatic injury due to ischemiareperfusion (Sharma et al 2003;Prince et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of genistein is exerted through the blocking of the estrogenic effect. However, in another study [146], genistein (10 mg/kg, 30 min before hemorrhagic shock) reduced kidney injury during ischemic shock in rats by inhibiting inflammation. However, the effect of genistein on vasoconstriction was not studied.…”
Section: The Effects Of Genistein On Kidney Ischemia/reperfusion Injurymentioning
confidence: 92%